2005
DOI: 10.1093/molbev/msi180
|View full text |Cite
|
Sign up to set email alerts
|

A Nuclear DNA Phylogenetic Perspective on the Evolution of Echolocation and Historical Biogeography of Extant Bats (Chiroptera)

Abstract: Bats (Order Chiroptera), the only mammals capable of powered flight and sophisticated laryngeal echolocation, represent one of the most species-rich and ubiquitous orders of mammals. However, phylogenetic relationships within this group are poorly resolved. A robust evolutionary tree of Chiroptera is essential for evaluating the phylogeny of echolocation within Chiroptera, as well as for understanding their biogeographical history. We generated 4 kb of sequence data from portions of four novel nuclear intron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
193
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(224 citation statements)
references
References 112 publications
16
193
2
5
Order By: Relevance
“…Therefore, the developmental programme that mobilizes adjacent muscular tissues for the precursors of the wing membranes might have been adopted in the initial phase of chiropteran evolution, in parallel with the acquisition of the wing itself. Furthermore, recent molecular phylogeny of extant bat species clearly identifies two major lineages within the order-suborders Yinpterochiroptera and Yangochiroptera 2,53,54 . In the present study, we revealed that the occipito-pollicalis of Miniopterus fuliginosus (family Miniopteridae), which is a member of Yangochiroptera, is solely innervated by cranial nerve VII.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the developmental programme that mobilizes adjacent muscular tissues for the precursors of the wing membranes might have been adopted in the initial phase of chiropteran evolution, in parallel with the acquisition of the wing itself. Furthermore, recent molecular phylogeny of extant bat species clearly identifies two major lineages within the order-suborders Yinpterochiroptera and Yangochiroptera 2,53,54 . In the present study, we revealed that the occipito-pollicalis of Miniopterus fuliginosus (family Miniopteridae), which is a member of Yangochiroptera, is solely innervated by cranial nerve VII.…”
Section: Discussionmentioning
confidence: 99%
“…These were then mapped on a pre-existing hypothesis of bat relationships. We used a tree (Miller-Butterworth et al, 2007) that is in broad agreement with two other major studies in molecular phylogenetics (Eick et al, 2005;Teeling et al, 2005). Our purpose was threefold.…”
mentioning
confidence: 99%
“…First, recent advances in molecular phylogenetics indicate that the order Chiroptera is monophyletic, putting to rest the idea of separate origins for the echolocating microbats and the nonecholocating, frugivorous megabats (Murphy et al, 2001;Eick et al, 2005;Teeling et al, 2005;MillerButterworth et al, 2007). Even evidence from other systems is overwhelmingly in support of bats as a monophyletic clade (Simmons, '94;Jones et al, 2002), although proponents of a separate Published online 14 May 2008 in Wiley InterScience (www.…”
mentioning
confidence: 99%
See 2 more Smart Citations